European structural and investment funds and regional convergence: The impact of public deficit in beta-convergence - Carlos San Juan Mesonada; Carlos Sunyer Manteiga (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2020)
The objective is to empirically assess the effects of the European Structural and Investment Funds (ESIF) on the regional convergence of income catching-up of the Objective 1 regions in Spain. The principal added value of the paper is that by using realized investment data, it allows comparison of the results in terms of real regional convergence of the two budgetary periods covering different phases of the business cycle and two ESIF operational programs. The panel data model's results allow recommendations to assess economic and financial adjustments in the UE and the use of the ESIF. Changes in economic cycles seem to have a significant impact on the ability of funds to contribute to the growth of the regional economy. Possible use in the Eurozone of the future Crisis Fund of the multiannual budget 2021-27. The level of indebtedness in the region has a definite adverse effect on the effectiveness of European projects. Additionally, we identify an apparent spillover effect from the funds towards other border regions on those that are formally receiving. Therefore, it is essential to be able to adapt the funds according to the phase of the business cycle. Moreover, during the downturns, to ensure their effectiveness may not be co-finance by regions.
Keywords: 330; Public Deficit; Income Gap; Regional Convergence; European Structural and Investment Funds; Regional Debt